Experimental Research on Acoustic Emission Characteristics and Felicity Effects during Coal Fatigue Failure under Cyclic Loading - Yongjie Yang; Luyi Xing (Advances in Materials Science and Engineering)
In order to study the acoustic emission characteristics and Felicity effect in the process of coal fatigue failure and reveal the internal relationship between the fatigue damage evolution law and the acoustic emission activity, with the help of MTS815.02 electrohydraulic servo rock mechanics test system and PCI-2 acoustic emission detection and analysis system, a triaxial cycling loading acoustic emission test was carried out on the coal samples. The results show that the higher the upper limit stress is, the more obvious the degree of fatigue damage will be caused by coal samples. At the same time, the more active acoustic emission signal will appear. The coal samples under linear loading are on the initial damage state, and slight fatigue, moderate fatigue, deep fatigue, and ultimate fatigue failure under cyclic loading. The acoustic emission shows the “L-” type development evolution law in any previous stress level range, while at the last stress level, it shows the obvious “U-” type development evolution law. The higher the frequency of the cyclic loading is, the higher the rate of initiation and expansion of the microcrack will be, while the more obvious acoustic emission phenomenon will appear. Furthermore, the ringing counting rate is basically the same as that of the energy counting rate. Under triaxial cyclic loading, a shear failure mode that extends along different directions of fracture surface will be presented. The acoustic emission in the range of different stress levels shows a different degree of Felicity effect. In contrast, it is more reasonable to use the principal stress difference as a parameter to study the Felicity effect of coal under cyclic loading.